IDENTIFIKASI MANGROVE DI WILAYAH PESISIR DESA BAGAN DALAM KABUPATEN BATU BARA - Puspitasari, Dian; Fajri, Surya; Satria, Indra; Hariyani, Riska; Lubis, Abdul Malik Kamarullah; Rumiati; Alfaresa, Aisyah; Mustofa, Nauval; Simanjuntak, Al Imran (JURNAL BIOSENSE, 2024)
Mangroves are an ecosystem environment located in tidal areas, where significant interactions occur between seawater, brackish water, rivers, and land. This interaction causes high diversity in the form of marine, freshwater, and terrestrial plants and animals in mangrove areas. Mangroves have many benefits, both ecologically and economically. The distribution of mangroves in Indonesia is very wide, including in the area of Batu Bara Regency, and information on mangrove identification in Batu Bara Regency, one of which is for Bagan Dalam village, is still minimal. The purpose of this study was to record the types of mangroves in Bagan Dalam village. The method used is an exploratory method, which records all types of mangroves in the research area. Mangroves in Bagan Dalam village consist of Acanthus ilicifolius species, Acrostichum speciosum, Avicennia marina, Clerodendrum inerme, Excoecaria agallocha, Morinda citrifolia, Nypa fruticans, Pluchea indica, Rhizophora apiculata, Sonneratia alba, Sonneratia ovata, Spinifex sp., Terminalia catappa, and Wedelia biflora. Water quality consists of temperature, pH, and salinity. The temperature value is 29.20C, the pH value is 7, and the salinity value is 18.2‰.